Phytocenotic features of Calluna vulgaris (L.) Hill. in Ukrainian Polesie - Lukash, Oleksandr; Melnyk, Viktor; Danko, Hanna; Rak, Oleksandr; Karpenko, Yurii; Buzunko, Petro (Ecological Questions, 2020)
Middle-aged pine and birch-pine forests of the Dicrano-Pinenion suballiance are the most common biotopes of Calluna vulgaris (L.) Hill. in Ukrainian Polesie. This species occurs mostly as solitary plants in forest phytocenoses; rarely its projective coverage can reach 40-45%. C. vulgaris has the highest constancy in phytocenoses of the Peucedano-Pinetum association in Right-bank Polesie. The forests of the Piceo-Vaccinienion uliginosi Seibert in Oberd. (ed.) 1992 suballiance and the Piceion excelsae Pawłowski et al. 1928 alliance are rare habitats of C. vulgaris; they occur only in Right-bank Polesie of Ukraine. Heathlands are rare ecosystems for Ukrainian Polesie, their vegetation is represented by plant communities of the Calluno-Ulicetea Br.-Bl. et Tx. ex Klika et Hadač 1944 and the Nardetea strictae Rivas Goday et Borja Carbonell in Rivas Goday et Mayor Lopez 1966 classes. They are forming in the significantly anthropogenically disrupted territories (e.g. areas after wildfires) or in the areas with intensive human activities, firstly in the military training areas. The phytocenoses of the Calluno-Genistetum pilosae R. Tx. 1937 association occur only in Right-bank Polesie and are the largest heathlands of Ukrainian Polesie in general. For example, in the Rivne region, their area is up to 20 km2. The area of heathlands, belonging to the Calluno-Nardetum strictae Hrync. 1959 association, does not exceed several hectares. The phytocenoses of the Scabioso canescentis-Genistetum Balcerk. et Brzeg 1993 association are represented with small plots in landscapes of pine forests and less frequently in mixed forests on upland terraces of Left-bank Polesie rivers. The characteristic feature of Calluna vulgaris spreading in Right-bank Polesie of Ukraine is its large participation (sometimes with the projective cover up to 80%) and high constancy (92,7%) in phytocenoses of oligotrophic bogs of the Ledo-Sphagnetum magellanici (Malc. 1929) Kästner et Flössner 1933 association. The populations of Calluna vulgaris, explored in the forest phytocenoses of the Cladonio-Pinetum Juraszek 1927 association on the territory of Ukrainian Polesie, are incomplete. Their age spectrum maximum falls on generative individuals. The “Right-bank” population of Calluna vulgaris are characterized by more active proliferation of plants and spreading on new territories. Aging processes dominate among the “left-bank” populations. Generally, environmental conditions of Ukrainian Right-bank Polesie are more favorable to Calluna vulgaris, than conditions of Left-bank Polesie.